Non-invasive Biomarkers of Liver Inflammation and Cell Death in Response to Alcohol Detoxification - Neuman, Manuela G.; Mueller, Johannes; Mueller, Sebastian (Frontiers in Physiology, 2021)
Introduction Alcohol-related liver disease (ALD) represents the most common liver disease worldwide, however, the underlying molecular mechanisms are still poorly understood. Namely centrilobular inflammation and programmed cell death are characteristic to ALD and it remains to be elucidated why they persist despite the absence of alcohol. Aims To study the effects of alcohol withdrawal in a cohort of heavy drinkers and the role of cirrhosis by using non-invasive biomarkers such as cytokines, apoptotic and angiogenic markers. Methods Caspase 3-cleaved M30, M65, cytokines (IL-6, IL-8), tumor necrosis factor alpha (TNF-α), transforming growth factor (TGF-β) and vascular endothelial growth factor (VEGF) were measured in 114 heavy drinkers. The role of alcohol detoxification was investigated in 45 patients. The liver histology was available in 23 patients. Fibrosis stage and steatosis were assessed by measuring liver stiffness (LS) and controlled attenuation parameter (CAP) in all patients using transient elastography (FibroScan, Echosens, Paris). Mean observation interval between the measurements was 5.7 ± 1.4 days (mean + –SD). Results Patients consumed a mean of 204 ± 148 g/day alcohol with a heavy drinking duration of 15.3 ± 11.0 years. Mean LS was 20.7 ± 24.4 kPa and mean CAP was 303 ± 51 dB/m. Fibrosis distribution was F0–38.1%, F1-2–31%, F3–7.1 and F4–23.9%. Apoptotic markers M30 and M65 were almost five times above normal. In contrast, TNF- α a, IL-8 and VEGF were only slightly elevated. Patients with manifest liver cirrhosis (F4) had significantly higher levels of M30, M65, IL-6 and IL-8. Histology features such as hepatocyte ballooning, Mallory-Denk bodies, inflammation and fibrosis were all significantly associated with elevated LS, and serum levels of TNF-alpha, M30 and M65 but not with CAP and other cytokines. During alcohol detoxification, LS, transaminases, TGF- β, IL-6, IL-8 and VEGF decreased significantly. In contrast, no significant changes were observed for M30, M65 and TNF- α and M30 even increased during detoxification in non-cirrhotic patients. Profibrogenic cytokine TGF-beta and pro-angiogenic cytokine VEGF showed a delayed decrease in patients with manifest cirrhosis. Conclusion Patients with alcohol-related cirrhosis have a pronounced apoptotic activity and a distinct inflammatory response that only partly improves after 1 week of alcohol detoxification. Alcohol withdrawal may represent an important approach to better dissect the underlying mechanisms in the setting of alcohol metabolism.